Análisis de la aplicación en producción audiovisual de los espacios naturales y recreativos en la ciudad de Babahoyo - Vera Vera, Susana Elizabeth (2020)
The present case study carried out on audiovisual production and recreational spaces in the city of Babahoyo allows us to know if these are applicable as recording places known as locations, thus allowing to expose these tourist places of the city allowing to expose them and know them through the image through the theoretical foundation that arises. The objective is to analyze the application of natural and recreational spaces in the city of Babahoyo in audiovisual productions, where data was obtained using qualitative research, a focus group was carried out with people from the city of Babahoyo, and 3 audiovisual professionals were also interviewed Through audiovisual production it seeks to overcome established ways to create, expose, share and deliver narratives. As a result, some recreational and natural spaces have been used in audiovisual productions such as the Gallery, Caleta, the Casa de Olmedo, evidencing that it is the most suitable place to produce audiovisual pieces such as advertising and music videos, etc.